Inheritance and genetic analysis of seed weight and associated traits in bambara groundnut (Vigna subterranea L.) genotypes - Atiqullah, Khaliqi (2021)
Knowledge of genetic variability within species of Bambara groundnut and the nature of breeding techniques are critical in this crop improvement programme. The importance of this information in underutilised crop species that mainly existing as landraces with limited information about their breeding systems and genetic diversity becomes important. Hence, this study was conducted to evaluate the genetic variability and to establish the relation between yield and its components in Bambara groundnut using multivariate analysis based on seed weight. To achieve this objective, firstly, a field trial was conducted in randomized complete block design with three replications on five Bambara groundnut genotypes from Nigeria, namely; Giwa, Duna, Cancaraki, Jatau, and Maiki. Prior to the field evaluation, the seeds of each genotype were grouped into three seed weight categories namely large, medium and small-seed size. In the second experiment, 28 lines were selected based on top grain yield plants from each seed weight category from first generation of the previous field evaluation. Data were collected on 25 agro-morphological traits and statistical analysis was conducted using SAS version 9.4 software for the analysis of variance, while variance component, genotypic and phenotypic coefficient variation, heritability and genetic advance values were estimated. Cluster analysis was performed using NT-SYS software to estimate the genetic relations among the Bambara groundnut lines. The present study revealed significant levels of variability among the genotypes, seed size categories and interaction of genotypes and seed size categories for most of the yield and yield components. High values of genotypic coefficient of variation (GCV≥20%) coupled with genetic advance (GA≥20%) was recorded for the number of medium seed weight per plant (GCV=36.76%, GA=36.15%), total large size seed weight per plant (30.34%, 28.26%), total medium size seed weight per plant (25.25%, 21.42%) and hundred seeds weight (20.02%, 29.29%), while moderate GCV (>10%) value was obtained for the total number of seed per plant (11.34%). Among the genotype and seed size combinations, G5S is the best for yield and yield component traits, while genotypes G3 is the best for yield and yield components, whereas among the seed size categories small seed size showed the high yield and yielding components. It was concluded from the second-generation progenies evaluation indicates that considerable amount of variation exists among Bambara groundnut cultivars for yield and yield components. Moderate broad sense heritability values couple with high genetic variance for growth traits such as wide plant canopy (52.17%) and number of branches (34.36%), while low broad sense heritability values (0 to 30%) were recorded for other traits. Almost all of the traits positively associated with the yield trait except the number of days to emergency, plant height, wide canopy, days to maturity, fresh and dried biomass weight. Finally, the lines evaluated were grouped into seven primary clusters using the unweighted pair group method with arithmetic mean (UPGMA) dendrogram based on the measured traits. Based on genetic diversity results and agronomic traits performance, improved lines, G5LR1P3, G1LR1P3, G4LR1P1, G2SR1P1 and G3SR1P4 performed best in terms of yield and yield components. These improved lines are recommended for large scale evaluation and utilisation in the future breeding programme for development of high yield Bambara groundnut varieties.